Decision support system (DSS) for water distribution management: theory and practice - Rey, J.; Hemakumara, H.M. (International Irrigation Management Institute, 1994)
The impact of information techniques in all economic activities has been tremendous during the past decade. However, the potential of the multiple management methods and technologies derived from this field has not been fully realized in the irrigation sector. One area of application of information techniques concern the design and installation of Decision Support Systems (DSS). This area, used for the particular activities relating to the management of water in irrigation schemes, constitutes the theoretical background of this paper